Collaborative Learning Strategies to Increase Religious Tolerance in Students: Building an Inclusive and Moderate Attitude in the Campus Environment - Ifham Choli (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
Collaborative learning is seen as an approach that emphasizes not only cognitive aspects but also develops students' affective and social dimensions through interaction, dialogue, and collaboration across perspectives. Through the collaborative process in heterogeneous groups, students not only learn to understand academic material but also learn to appreciate differences, build empathy, and develop mutual respect in the context of religious diversity. This study aims to examine in depth the role of collaborative learning as a strategic tool in fostering religious tolerance among students at As-Syafi'iyah Islamic University. Amidst the social dynamics and diverse religious backgrounds of students, the campus as an intellectual space has a moral and pedagogical responsibility to shape moderate, open, and inclusive characters. This study uses a qualitative, descriptive-analytical research approach. This approach was chosen because it allows researchers to explore in depth the experiences, views, and attitudes of students and lecturers in implementing collaborative learning. The results show that collaborative learning can create a safe, equal dialogue space for students to express their religious views while understanding others' perspectives. Intensive interaction in heterogeneous groups fosters mutual trust, empathy, and openness, ultimately strengthening religious tolerance.